2010
DOI: 10.1029/2010gl042716
|View full text |Cite
|
Sign up to set email alerts
|

Observational evidence for propagation of decadal spiciness anomalies in the North Pacific

Abstract: The propagation of density‐compensated (warm/salty or cool/fresh) spiciness anomalies in the North Pacific thermocline is investigated using Argo profiles for the period 2001–2008. A cool/fresh spiciness anomaly on 25 < σθ < 25.5 kg m−3 isopycnals appears in the eastern subtropical North Pacific at 120°W–150°W in 2003–2004 with a salinity anomaly of about −0.15 PSS‐78. This spiciness anomaly migrates southwestward, and arrives in the western tropical North Pacific at 145°E–175°W in 2008 with the salinity anoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
63
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 36 publications
19
63
0
1
Order By: Relevance
“…It is likely that the TA signal propagates as Rossby waves on interannual time scale but circulates by horizontal advection on decadal time scale. Recent Argo observation seems to support this speculation [Sasaki et al, 2010].…”
Section: Connection With the Tropical Oceansupporting
confidence: 52%
“…It is likely that the TA signal propagates as Rossby waves on interannual time scale but circulates by horizontal advection on decadal time scale. Recent Argo observation seems to support this speculation [Sasaki et al, 2010].…”
Section: Connection With the Tropical Oceansupporting
confidence: 52%
“…Analyses of Argo data have revealed robust spatial-temporal characteristics of regional and basin-scale spiciness variability (e.g., Johnson, 2006;Yeager and Large, 2007;Sasaki et al, 2010;Kolodziejczyk and Gaillard, 2012;Li et al, 2012aLi et al, , 2012bKatsura et al, 2013;Kolodziejczyk et al, 2014). Anomalies with large magnitudes are formed in the eastern Pacific basin in both hemispheres and communicated to the central equatorial Pacific by the interior equatorward flow (Johnson and McPhaden, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…While most of the existing researches were focused on the spiciness variations in the Pacific Ocean (e.g., Schneider et al, 1999;Schneider, 2000Schneider, , 2004Kessler, 1999;Yeager and Large, 2004;Luo et al, 2005;Sasaki et al, 2010;Gaillard, 2012, 2013) or the Atlantic Ocean (e.g., Lazar et al, 2001;Laurian et al, 2006Laurian et al, , 2009Kolodziejczyk et al, 2014), their counterpart in the Indian Ocean has never been examined before. However, the important role of the tropical Indian Ocean (TIO) in global climate has been increasingly recognized (e.g., Annamalai et al, 2007;Xie et al, 2009;Luo et al, 2010Luo et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to understand salinity variability mainly focused on sea surface salinity (SSS) in the tropical oceans (Delcroix & Hénin, 1991;Dessier & Donguy, 1994;Delcroix et al, 1996;Johnson et al, 2002). Recently, with the availability of an increased number of salinity observations, more studies have focused on the subsurface salinity budget and its variability (Lukas, 2001;Foltz et al, 2004;Phillips et al, 2005;Foltz & McPhaden, 2008;Ren & Riser, 2010;Sasaki et al, 2010;Kilpatrick et al, 2011). For example, Lukas (2001) examined salinity observations near the Hawaii Ocean Time Series (HOT) station and reported that from 1988 to 2001 the main thermocline near the HOT station experienced a pronounced freshening, which is related to the subduction of surface salinity anomalies at higher latitudes.…”
Section: Introductionmentioning
confidence: 99%